Primary angiitis of the CNS and reversible cerebral vasoconstriction syndrome: A comparative study. (16th October 2018) - de Boysson, Hubert; Parienti, Jean-Jacques; Mawet, Jérôme; Arquizan, Caroline; Boulouis, Grégoire; Burcin, Cécilia; Naggara, Olivier; Zuber, Mathieu; Touzé, Emmanuel; Aouba, Achille; Bousser, Marie-Germaine; Pagnoux, Christian; et al.
Abstract : Objectives: To further improve the distinction between primary angiitis of the CNS (PACNS) and reversible cerebral vasoconstriction syndrome (RCVS). Methods: We compared 2 large French cohorts of patients with PACNS (n = 110, retrospectively and prospectively enrolled) and RCVS (n = 173, prospectively enrolled). Results: Patients with RCVS were predominantly female ( p < 0.0001), with migraines ( p < 0.0001), and were more often exposed to vasoactive substances ( p < 0.0001) or postpartum ( p = 0.002) than patients with PACNS. Headache, especially thunderclap headache, was more frequent in RCVS (both p < 0.0001). Thunderclap headache was absent in only 6% of patients with RCVS and was mainly recurrent (87%) and provoked (77%) mostly by sexual intercourse, exertion, or emotion. All other neurologic symptoms (motor deficit, seizure, cognitive disorder, or vigilance impairment, all p < 0.0001) were more frequent in PACNS. At admission, brain CT or MRI was abnormal in all patients with PACNS and in 31% of patients with RCVS ( p < 0.0001). Acute ischemic stroke was more frequent in PACNS than in RCVS ( p < 0.0001). Although intracerebral hemorrhage was more frequent in PACNS ( p = 0.006), subarachnoid hemorrhage and vasogenic edema predominated in RCVS ( p = 0.04 and p = 0.01, respectively). Multiple small deep infarcts, extensive deep white matter lesions, tumor-like lesions, or multiple gadolinium-enhanced lesions were observed only in PACNS, whereas cervical artery dissection was found only in RCVS. Conclusions: Our study confirms that careful analysis of clinical context, headache features, and patterns of brain lesions can distinguish PACNS and RCVS within the first few days of admission in most cases. However, diagnosis remains challenging in a few cases.